Kecerdasan Intelektual, Kecerdasan Emosional, Kecerdasan Spiritual Dan Organizational Citizenship Behavior Terhadap Kinerja Pegawai - Mawar Ratih Kusumawardani; Brahma Wahyu; Bambang Suwarsono (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2021)
Performance is the one thing to measure succesul of an organization. Effort to Improve the performance its very important to achieved organization goal. Efforts to improve performance are not easy to achieve because it is influenced by many factors including factors that come from the employees itsself likes intellectual quotients, emotional quotients, spiritual quotients and organizational citizenship behavior. These factors are very important to noticed, they are expected to make more contribute to improving performance. This research was conducted all 71employees of the General Section of the Regional Secretariat of the City of Kediri. Data was obtained through observation, interviews and questionnaires. This study uses multiple linear regression analysis, with the results obtained: intellectual quotients (IQ) does not partially affect employee performance, emotional quotients (EQ) partially affects employee performance, spiritual quotients (SQ) does not affect partially partially on employee performance, organizational citizenship behavior (OCB) has a partial influence on employee performance, and simultaneously intellectual quotients (IQ), emotional quotients (EQ), spiritual quotients (SQ) and organizational citizenship behavior (OCB) affect employee performance.